Evolutionary history of sexual selection affects microRNA profiles in Drosophila sperm. (3rd January 2022) - Hotzy, Cosima; Fowler, Emily; Kiehl, Berrit; Francis, Roy; Mason, Janet; Moxon, Simon; Rostant, Wayne; Chapman, Tracey; Immler, Simone
Abstract: The presence of small RNAs in sperm is a relatively recent discovery and little is currently known about their importance and functions. Environmental changes including social conditions and dietary manipulations are known to affect the composition and expression of some small RNAs in sperm and may elicit a physiological stress response resulting in an associated change in gamete miRNA profiles. Here, we tested how microRNA profiles in sperm are affected by variation in both sexual selection and dietary regimes in Drosophila melanogaster selection lines. The selection lines were exposed to standard versus low yeast diet treatments and three different population sex ratios (male‐biased, female‐biased, or equal sex) in a full‐factorial design. After 38 generations of selection, all males were maintained on their selected diet and in a common garden male‐only environment prior to sperm sampling. We performed transcriptome analyses on miRNAs in purified sperm samples. We found 11 differentially expressed miRNAs with the majority showing differences between male‐ and female‐biased lines. Dietary treatment only had a significant effect on miRNA expression levels in interaction with sex ratio. Our findings suggest that long‐term adaptation may affect miRNA profiles in sperm and that these may show varied interactions with short‐term environmental changes.